Rapidly progressive aortic valve regurgitation - a case report - Klimek, Monika; Knap, Joanna; Rabiej, Paulina; Prasał, Marek (Journal of Education, Health and Sport, 2018)
In this paper we present a case report of a 73-year-old patient with a multifocal predisposition (rapidly progressing aortic regurgitation associated with tricuspid and mitral valve regurgitation) and 2-vessel ischemic heart disease.